(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
This article analyses the definition of fraud as an exception to the principle of indefeasibility of title under section 340(2) NLC with special reference to the effect of notice on unregistered interest. An analysis of decided cases regarding court standing as to the position of unregistered parties in Malaysia is also made for a holistic look at the importance of "knowledge or notice" of unregistered interest in the concept of indefeasibility of title according to land law. This article also highlights some proposed solutions for the protection of unregistered interest. Keywords: fraud, unregistered interest, case analysis, solutions and conclusion